On the asymptotic equilibrium and asymptotic equivalence of differential equations in Banach spaces - Nguyen Sinh Bay; Nguyen The Hoan; Nguyen Minh Man (Український математичний журнал, 2008)
We present some conditions for the asymptotic equilibrium of nonlinear differential equations in Banach spaces, in particular, of the linear nonhomogenous equation. We also discuss analogous problems for the linear equation with a nonbounded operator. Some obtained results are applied to problems of asymptotic equivalence.